The “Christening” of Ancient Baltic Religion in Kazys Bradūnas’s Poetry - Čiočytė, Dalia (Colloquia, 2017)
Baltic cultural history is marked by deep tensions between ancient religion and Christianity. These tensions are explored in Lithuanian literature, which reveals their drama and tragedy and/or “christens” the old faith by drawing connections between it and Christianity. The most distinct poetic version of this kind of “christening” is the poetry of Kazys Bradūnas (1917–2000); the author of this article discusses Bradūnas’s oeuvre through the lens of literary theology, a discipline which uses theological and aesthetic criteria to study how literature explores questions around transcendence. Bradūnas brings to light non-Christian apostolic manifestations in Baltic culture, in the pillaging and murder that took place under the guise of prostelatizing, and reveals the deep connections between the ancient Baltic and Christian world-views. If, for Bradūnas, a Christian poet, Christianity is a revealedreligion, one that has been given, he sees the old faith – an intuitive quest for the essence of humanity using only human means – as an expression of his people’s distinct character. This determination to articulate the nation’s distinct culture as a form of mentality is the clear intention of Bradūnas’s poetry. In commenting on the distinct nature of Lithuanian and Baltic culture the poet focuses on three aspects: creativity, agrarianism, and statehood. The most artistically important figure to emerge from the dialogue between the old faith and Christianity is the main character from the original mythological story of the grass snake Žilvinas – a betrayed and murdered metaphysical king. The connection between Žilvinas and Christ activates primordial Baltic cultural experience and paves the way for a Lithuanian conception of Christ. Žilvinas is an important figure in Christianity’s inculturation in Lithuania and evidence of how primordial Baltic experience enriched the reception of Christ. In making typological connections between the experience of the Crusades and the aggression of Russian communism, and searching for meaning in suffering, the poet draws on the Christian concept of suffering.